(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
Eight new species (Ripersiella hambletoni, R. kaydani, R. loksae, R. madagascarella, R. monticola, R. ruandaensis, R. salvatorei, and R. seychelliella) are described, R. periolana redescribed and 15 new combinations proposed. The internal structure of female genital organ was studied in some species and the rate and shape of chitinisation are also used as a specific character. A review of the genus, a key for the 73 species, a map of distribution, with some phylogenetic and zoogeographic comments are given.